When i turned six - Drew, David; Power, Margaret (Nelson Australia South Melbourne, Vic., 1994)
A child compares her sixth birthday to the sixth birthdays of Mom, Grandma, and Great-Grandma, revealing the fashion trends and characteristics of previous decades